THE ARCTIC – THE MIDDLE KINGDOM’S AREA OF INTEREST - ELAK Leszek; ŚLIWA Zdzisław (2018)
Arctic region is one of areas of interest of China and it is connected with politics and economy as for now. Recognizing emerging options especially in the latter domain the country is looking for possibilities to ensure national interests in the long-term perspective. It is linked with using variety of tools to engage regional actors bilaterally and in organizational framework without involving military instrument of power. Parallel, China is developing technologies necessary to operate in the Arctic allowing competing with other players. It includes research and investments in the region. Natural resources, sea lines of communication, opportunities for fishery are among factors requiring preservation of national benefits and it is achievable only by grounded presence in many dimensions.